A novel integration of a green power-to-ammonia to power system: Reversible solid oxide fuel cell for hydrogen and power production coupled with an ammonia synthesis unit. (20th May 2021) - Mukelabai, Mulako Dean; Gillard, Jonathon M.; Patchigolla, Kumar
Abstract: Renewable energy is a key solution in maintaining global warming below 2 °C. However, its intermittency necessitates the need for energy conversion technologies to meet demand when there are insufficient renewable energy resources. This study aims to tackle these challenges by thermo-electrochemical modelling and simulation of a reversible solid oxide fuel cell (RSOFC) and integration with the Haber Bosch process. The novelty of the proposed system is usage of nitrogen-rich fuel electrode exhaust gas for ammonia synthesis during fuel cell mode, which is usually combusted to prevent release of highly flammable hydrogen into the environment. RSOFC round-trip efficiencies of 41–53% have been attained when producing excess ammonia (144 kg NH3 /hr) for the market and in-house consumption respectively. The designed system has the lowest reported ammonia electricity consumption of 6.4–8.21 kWh/kg NH3, power-to-hydrogen, power-to-ammonia, and power-generation efficiencies of 80%, 55–71% and, 64–66%. Graphical abstract: Image 1 Highlights: P2A to power system enhances renewable energy usage by solving intermittency issues. Optimum P2A to power system design and operating parameters determined. Argon-free nitrogen resulting to non-limiting Haber Bosch recycle-loop fraction. Novel system has lowest reported ammonia synthesis electricity consumption. High power-to-ammonia efficiency attained, and excess ammonia available for market.